2009
DOI: 10.1186/1742-4755-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian network for the surveillance of maternal potentially life threatening morbidity and maternal near-miss and a multidimensional evaluation of their long term consequences

Abstract: This project has two components: a multicenter, cross-sectional study to be implemented in 27 referral obstetric units in different geographical regions of Brazil, and a concurrent cohort study of multidimensional analysis. Over 12 months, investigators will perform prospective surveillance to identify all maternal complications. The population of the cross-sectional component will consist of all women surviving potentially life-threatening conditions (severe maternal complications) or life-threatening conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 23 publications
2
75
1
18
Order By: Relevance
“…3 Haemorrhage is reported to be the leading cause of maternal death in Japan and Europe as a whole and the third most common cause of death in the United States. 6 Another study 2 reported the rate of major obstetrical haemorrhage as 4.5 per 1000 deliveries, whereas it was 3.23 per 1000 deliveries in our study. Admission to MICU was 14.47% in our study compared to 27% for major obstetrical haemorrhage in the abovementioned study.…”
Section: -11contrasting
confidence: 50%
See 1 more Smart Citation
“…3 Haemorrhage is reported to be the leading cause of maternal death in Japan and Europe as a whole and the third most common cause of death in the United States. 6 Another study 2 reported the rate of major obstetrical haemorrhage as 4.5 per 1000 deliveries, whereas it was 3.23 per 1000 deliveries in our study. Admission to MICU was 14.47% in our study compared to 27% for major obstetrical haemorrhage in the abovementioned study.…”
Section: -11contrasting
confidence: 50%
“…WHO describes it as near-death but survival from complications which occurred during pregnancy, childbirth or within 42 days of termination of pregnancy. 1,2 Each year nearly 5,29,000 women die globally due to pregnancy causes. For each death, nearly 118 women suffer from life threatening events.…”
Section: Introductionmentioning
confidence: 99%
“…O viés gerado pelas subnotificações de morte materna na interpretação dos índices ao longo do tempo foi devido à melhora dos registros após a criação de diversos comitês de mortalidade materna no país, e assim os óbitos passaram a ser mais rigorosamente notificados, mascarando a redução na razão de mortalidade materna real em relação à dos dias atuais. No passado morriam mais mulheres, porém pelo sub-registro, a razão de mortalidade materna estava subestimada 8 . Pensando em uma maneira de melhor avaliar a assistência a essas mulheres que morrem e de ter uma compreensão mais global do problema, com um maior número de casos avaliados, desenvolveu-se o conceito de near miss materno.…”
Section: Introductionunclassified
“…Cecatti et al 8 construíram algumas hipóteses sobre os efeitos do near miss à mãe e ao bebê. As mulheres teriam maior probabilidade de sofrer estresse pós-traumático, depressão pós-parto e comprometimento de suas vidas sexuais.…”
Section: Mulheres Que Vivenciaram O Near Miss Materno Podem Por Meiounclassified